An automatic peak deconvolution method for Raman spectra of terrestrial carbonaceous material for application to the geothermometers of Kouketsu et al. (2014). (20th November 2022) - Kaneki, Shunya; Kouketsu, Yui
Abstract: Carbonaceous material undergoes changes in its maturity mainly in response to its thermal history. Among the various geothermometers based on Raman spectra of carbonaceous material, those proposed by Kouketsu et al. (2014) have been employed to investigate the temperatures experienced by terrestrial rocks that undergo low‐ to medium‐grade metamorphism. Although their geothermometers use spectral parameters that can be determined only by peak deconvolution, criteria for setting the initial conditions for nonlinear least‐squares fitting have not been specified, which may generate unnecessary errors in the estimated temperatures owing to differences in fitting results among data analysts. To address this issue, we developed a code that automatically calculates the parameters required for the geothermometers of Kouketsu et al. (2014); that is, the widths of the D1‐ and D2‐bands. Our code yields parameter values consistent with those of Kouketsu et al. (2014) for the same Raman data and is applicable to datasets other than those used to develop it. The geothermometers based on the obtained results show a comparable performance to Kouketsu et al. (2014). Errors in the estimated temperatures caused by variation in Raman systems and the subjective selection of the fitting method are smaller than the uncertainties of the geothermometer itself, so long as the temperature is calculated by following the procedures of the present study. Although this study focused only on geothermometers that require peak deconvolution, the development of those based on fitting‐free Raman parameters and on the reaction kinetics of carbonaceous material should be investigated in future studies.